Вы находитесь на странице: 1из 742

Murray Klamkin, Amer. Math. Monthly

Richard K. Guy

June 22, 2006

This is the third of a number of ﬁles listing problems, solutions and other writings of Murray Klamkin.

LAST UPDATED 2006-06-21 (Summer solstice)

The easiest way to edit is to cross things out, so I make no apology for the proliferation below. Just lift out what you want.

Amer. Math. Monthly, 56(1949) 347–348. Summation, Binomial coeﬃcients

4276 [1947,601]. Proposed by P. A. Piz´a, San Juan, P.R.

Let the integers

n K c be deﬁned by the relations

n K 1 = 1;

n K m = 0,

m > n;

Prove the following summations

(A) x n

x1

(B)

a=1

n+1 K c = c( n K c +

n K c1 ),

=

n

j=1

n

=

j=1

n K j x

j

n K j

j + 1

x

1

c > 1

Solution by M. S. Klamkin, Brooklyn Polytechnic Institute, Brooklyn, N.Y.

On the assumption that (A) is true, we have

x n+1

=

n

j=1

n K j x

j

x =

n

j=1

n K j (j + 1)

j + 1 + j x

j

x

=

n K 1 x +

n

j=2

x

j

= n+1 K 1 x +

n

j=2

[j ·

n K j + j ·

n K j1 ] + (n + 1) n K n

n + 1

x

n+1 K j x +

j

n+1 K n+1

n + 1 =

x

n+1

j=1

n+1 K j x

j

Since (A) is evidently true for n = 1, it is true for all n by induction.

(B) follows immediately from (A) by use of the familiar relation

Thus

x1

a=1

a n =

x1

n

a=1

j=1

n K j

x1

a=j

=

a

j

j + 1

x

a

j

=

n

j=1

n K j

x1

a=1

a

j

=

n

j=1

n K j

j + 1

x

Solved also by [6 others, including] E. T. Frankel and Yu-shu Luan.

Frankel points out that (A) and (B) are special cases of general formulas in the calculus of ﬁnite diﬀerences which express the general term and the sum of a given number of terms of a rational integral function by meansof its leading diﬀerences and binomial coeﬃcients. (See Whittaker and Robinson, The Calculus of Observations, London,

1924, p.7.) The integers n K 1 , n K 2 , powers of the natural nombers 0 n , 1 n , 2 n ,

In consequence, as noted by Yu-shu Luan, we have the following explicit expression for

n K c

., n K c are the leading diﬀerences of the n th ., c n .

n K c =

n

j=1

(1) j

2

c

j

(c j) n

Amer. Math. Monthly, 56(1949) 474–475. The Sum of a Series

E 844 [1949, 31]. Proposed by Orrin Frink, Pennsylvania State College

Sum the series

1 + 1/5! + 1/10! + 1/15! + · · · + 1/(5n 5)! + · · ·

II. Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. Since the sum of the m th powers of the k k th roots of unity is zero unless m is a multiple of k, in which case the sum is unity, we have, from the Maclaurin expansion of e z

k

j=1

exp(w k

j x) = k

n=0

x kn /(kn)!

where w k is a primitive k the root of unity. The required sum, obtained by taking x = 1, k = 5, is then

S = (1/5)

5

j=1

exp w j

5

Also solved by [21 others]

Several solvers easily reduced the above sum to

S = (1/5)[e + 2e cos 72 cos(sin 72 ) + 2e cos 36 cos(sin 36 )]

 If we are merely interested in obtaining a numerical result, however, there is little point of transforming the original series, which converges very rapidly. Thus four terms of

the series gives S = 1.00833360890

[F. C. ]Smith picked up, as a by-product, the pretty summations

n=0

n=0

(x n cos )/n! = e x cos θ cos(sin θ)

(x n sin )/n! = e x cos θ sin(sin θ)

[[RKG notes that the above numerical value is given by three terms. Four terms give 1.008333608907290289 and ﬁve terms give 1.0083336089072902899764536]]

3

Amer. Math. Monthly, 56(1949) 634. A series for π

E 854 [1949, 104]. Proposed by Jerome C. R. Li, Oregon State College

Show that π = n=0 (n!) 2 2 n+1 /(2n + 1)!

[[Five solutions were published, one by Ragnar Dybvik using the beta function, the second by Paul Carnahan using Wallis’s formula, the third by Murray below, the fourth by N. J. Fine using a diﬀerential equation, and the ﬁfth by D. H. Browne using Euler’s transfomation of series.]]

III. Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. (Using the Legendre polynomials). We have

1

a n = (n!) 2 2 n+1 /(2n + 1)! =

1

z n P n (z) dz

where P n (z) is the Legendre polynomial of degree n. Therefore

n=0

1

a n =

1

n=0

1

z n P n (z) dz =

1

4

(1 z 2 ) 1/2 dz = π

Amer. Math. Monthly, 57(1950) 39. Equivalent Concurrent Sections of a Tetrahedron

E 865 [1949, 263]. Proposed by Victor Th´ebault, Tennie, Sarthe, France

Find a point such that the planes drawn through this point parallel to the faces of a tetrahedrn cut the opposite trihedrals in equivalent triangles. Express the common area of these triangles in terms of the areas of the faces of the tetrahedron.

Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. Denote the areas of the faces of the tetrahedron by A i (i = 1, 2, 3, 4), the corresponding altitudes by H i and the perpendicular distances from the corresponding vertices to the corresponding plane sections by h i . Let V be the volume of the tetrahedron and A the common area of the parallel sections. Then

Therefore

(H i h i )A i = 3V + H i A i

h

2

i

2

/H

i

= A/A i

3V = H i A i H i (AA i ) 1/2 = 12V H i (AA i ) 1/2

or

Also

A 1/2

=

9V/ H i A

1/2

i

= 3 A

h i = 3H i A

1/2

i

A

1/2

i

1/2

i

The analogous problem for the plane was proposed by J. Neuberg as Question 30, Mathesis, 1881, p.148. For this case we have

2/k = 1/a + 1/b + 1/c

where a, b, c are the sides of the triangle and k is the common length of the concurrent lines which are drawn parallel to the sides of the triangle. This, and the result of the given problem, suggested to [N. D. ]Lane for the corresponding problem of an n-dimensional simplex the formula

n/k = 1/a

where k n1 is the common content of the (n 1)-dimensional cells parallel to the (n 1)-dimensional cell “faces” of the simplex, and a n1 is the content of a “face”.

[[I pause to note that Murray does not appear in the Author Index in Amer. Math. Monthly, 57 No.7, part 2: index of Vols. 1 to 56, Aug-Sep 1950.]]

5

Amer. Math. Monthly, 58(1951) 195.

4431. Proposed by M. S. Klamkin, Brooklyn Polytechnic Institute, New York

If S n = n 1/r, prove

1

n=1

S

n

n 2

= 2

n=1

1

n 3 = 2

n=1

S

n

(n + 1) 2

Amer. Math. Monthly, 59(1952) 471–472. A Summation Problem

Solution by Robert Steinberg, University of California, Los Angeles. It suﬃces to prove the ﬁrst and third expressions equal since the obvious identity

n=1

S n

n 2 =

n=1

1

n 3 +

n=1

S n

(n + 1) 2

implies the second. Now we have

n=1

S n

n 2

=

=

n=1

1

n

2

n=1

r=1

n

r=1

1

r =

1

n=1

1

n 2

r=1

1

r

n + r

1

n=1

r(n + r) 2 + n(n + r) 2 = 2

1

∞ ∞

r=1

1

r(n + r) 2

by symmetry. Upon setting r = R and r + n = N + 1, with appropriate changes in the limits of summation, this last form becomes 2 S N /(N + 1) 2 and the proof is complete.

An interesting corollary may be obtained as follows. We have

1

n=1

S n

n 2 =

n

n=1

r=1

1

n 2 r

If the indicated summation in the (n, r)-plane is carried out along rational rays through the origin, the ﬁrst integral point on such a ray is a point (R, N ) such that R and N are relatively prime and all other points on this ray are the integral multiples of (R, N ). Thus the contribution of this ray to the sum is

1

N

2 R

n=1

1

n

3

The contribution of all rational rays with 0 < R N is thus

n=1

1

n

3

1

N

2 R

6

(1)

where the inner summation is made over all pairs of integers R and N such that 0 < R N and R and N are relatively prime. Since the expression (1) is equal to 2 1/n 3 we get the desired result:

1

1

2 R = 2.

N

[[Also solved by [5 others and] the proposer.]]

Editorial Note. [J. ]Vales and [A. ]Petracca obtain the following generalizations. Put

S(r, n) =

n

i=1

1

i r

with K(1, n) = 1/n. Then

n=1

1

n h+2 =

h

n=1

i=1

[D. H. ]Browne ﬁnds

n=1

S

n

n 3 =

n=1

K(r, n) =

S(i, n) (n + 1) h+2i

1

n + r 1

n

i=i

n=1

1

n h+1 =

K(r 1, i)

n=1

K(h, n)

h + n 1

1

n 4 +

n=1

S

n

(n + 1) 2 = 5

n=1

S

n

(n + 1) 3

but further extensions do not assume so neat a form.

7

Amer. Math. Monthly, 58(1951) 260.

 E 963. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn It had started snowing before noon and three snow plows set out at noon, 1 o’clock

and 2 o’clock, respectively, along the same path. If at some later time they all came together simultaneously, ﬁnd the time of meeting and also the time it started snowing.

Amer. Math. Monthly, 59(1952) 42. A Variation of the Snow Plow Problem

Solution by L. A. Ringenberg, Eastern Illinois State College. Let n denote thenumber

of hours before noon that it started to snow and let x, y, z denote the distances that

the ﬁrst, second and third snow plow travelled by t hours past noon. Assume that it snows at a constant rate. Then, if the length units are properly chosen, we have

dt/dx = t + n,

x = 0

when

t = 0

 with solution t = e x n − n (1) Also dt/dy = t − (e y n − n), y = 0 when t = 1 with solution t = e y (n + 1 − ny) − n (2) Also dt/dz = t − [e z (n + 1 − nz) − n] z = 0 when t = 2 with solution

t = e z (n + 2 nz z + nz 2 /2) n

(3)

Let d denote the common value of x, y and z when the plows meet and let T denote the value of t when the meeting occurs. It follows from (1), (2) and (3) that

(T + n)/e d = n = n + 1 nd = n + 2 nd d + nd 2 /2

Solving we get n = 1/2 and T = 3.195. Therefore it began to snow at 11:30 and the plows met at about 3:12.

[[Solved by [5 others and] the proposer.]]

8

Amer. Math. Monthly, 58(1951) 261. Tetrahedron and Concurrent Cevians

E 928 [1950, 483]. Proposed by Victor Th´ebault, Tennie, Sarthe, France

Given a tetrahedron ABCD and a point O. Denote by A , B , C , D the intersections of AO, BO, CO, DO with the corresponding faces of the tetrahedron, and set x =

AO/A O, y

= BO/B O, z = CO/C O, t = DO/D O. Show that

xyzt = 3 2(x + y + z

+ t) + (xy + xz

+ xt + yz + yt + zt).

Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. The altitude of OBCD from O is easily shown to be h A /(1 x), where h A is the altitudeof ABCD from A. Therefore, if V is the volume of ABCD and b A is the area of the face opposite A,

V = (h A b A )/3(1 x) = V/(1 x)

That is

1 = 1/(1 x) + 1/(1 y) + 1/(1 z) + 1/(1 t)

or

xyzt = 3 2(x + y + z + t) + (xy + xz + xt + yz + yt + zt).

9

Amer. Math. Monthly, 58(1951) 268–269. Two summations

4356 [1949, 479]. Proposed by P. A. Piza, San Juan, Peurto Rico

Prove the relations

(a)

(b)

x 2n+1 (x 1) 2n+1 =

x 2n+2 (x 1) 2n+2

=

n

a=0

n + a 1 + n + 1 + a

2a +

2a + 1

(x 2 x) na

(2n 1)

n

a=0

n + a 2a +

1 (x 2 x) na

[[The last binomial is misprinted 2a+1 in the original. — R.]]

II. Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn, New York. Assume

(b) is true for n = k. Then by integrating between 1 and x we obtain

n+1

x 2n+1 (x 1) 2n+1 = 1 +

k

a=0

2k + 3 a k + 1 + a

k + 1

2a + 1

(x 2 x) k+1a

which is easily shown to be equivalent to (a) for n = k + 1. Further, upon multiplying

(a) for n = k + 1 by 2x + 1, multiplying (b) for n = k by x 2 x, and subtracting, we

get exactly (b) for n = k + 1. Since (a) and (b) are obviously true for n = 0, it follows by induction that they are true for all integral n.

10

Amer. Math. Monthly, 58(1951) 569.

4455. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn

f(x) = f (x)

g (x)

g(x)

solve for f (x) in terms of g(x) and for g(x) in terms of f (x). (This is an extension of one of the problems proposed for th 1951 William Lowell Putnam Prize Competition.)

Amer. Math. Monthly, 59(1952) 707.

Functions such that the Derivative of the Quotient is the Quotient of the Derivatives

Solution by E. J. Scott, University of Illinois. Using the abbreviations f , g, f , g for f (x), g(x), etc., we have

from which

(gf fg /g 2 = f /g )

(1)

f /f g /g = [1 g/g ] 1

Integrating, we have

ln f/g = [1 g/g ] 1 dx

whence

f = g exp [1 g/g ] 1 dx

Similarly, from (1) we obtain

(g /g) 2 (f /f )(g /g) + f /f = 0

whence

(g /g) 2 =

2 1 f /f ± (f /f ) 2 4(f /f )

Integrating and solving for g, we get

g

= f exp ± 1 2 (f /f ) 2 4(f /f ) dx

Also solved by [7 others] and the Proposer.

11

Amer. Math. Monthly, 59(1952) 408. A Slow Ship Intercepting a Fast Ship

E 991 [1951, 699]. Proposed by C. S. Ogilvy, Syracuse University

Two ships leave diﬀerent points at the same time and steam on straight courses at constant but unequal speeds. Find the condition under which the slower ship can intercept (catch) the faster.

Solution by M. S. Klamkin, Brooklyn Polytechnic Institute. If the slower ship intercepts the faster ship then the ratio of the distances traversed is V S /V F , where V S is the velocity of the slow ship and V F is the velocity of the fast ship. But the locus of a point such that the ratios of its distances from two ﬁxed points is constant, is a circle. Thus if the path of the faster ship intersects this circle it can be intercepted by the slower one.

Editorial Note. The circle is a circle of Apollonius of the two starting points. If θ is the angle between the faster ship’s course and the line joining the two starting points,

then it is easily shown that the slower ship can set a course to intercept the faster ship

 if and only if θ ≤ arcsin(V S /V F ). If we have inequality here, then there are two courses that the slower ship may set. The

problem become more interesting if the sphericity of the earth is taken into account.

Amer. Math. Monthly, 59(1952) 636. An Approximation for

E 1004 [1952, 105]. Proposed by L. R. White, Washington, D.C.

(1) The approximation

and frequently used. Show that for large n and all a

n

a

n a = 1 + (a 1)/n for large n and a close to 1 is well known

n a = 1 + (ln a)/n

is a good approximation.

(2) Find

n (k 1 +

lim

a)/k n

n

Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. (1) For all a > 0

n a = e (ln a)/n = 1 + (ln a)/n + O(1/n 2 )

(2) Using the preseding result we ﬁnd

n lim (k 1 +

a)/k n

n

=

n lim 1 + (ln a)/kn + O(1/n 2 ) n

= e (ln a)/k = a 1/k

12

Amer. Math. Monthly, 59(1952) 637. An Application of the Newton-Raphson Method

E 1005 [1952, 105]. Proposed by D. W. Dubois, University of Oklahoma

Let x 0 = 0 and a > 0 be two real numbers. Deﬁne

x n+1 = x n /2 + a/2x n

n = 0, 1, 2,

Find all values of x 0 and a for which the sequence {x n } converges, and ﬁnd the limits.

II. Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. If we plot y = x/2 + a/2x and y = x we get a geometric insight into the convergence process. The curve is a hyperbola with x = 0 and y = x/s as the asymptotes. The intersections

are ( a, a) and ( a, a). Also, the points of intersection are the maximum and minimum points of the hyperbola. From the plot it follows that the sequence converges

for all values of a > 0 and x 0 = 0. If x 0 > 0, then x n a; if x 0 < 0, then x n → − a.

[[ [R. E. ]Greenwood called attention to Whittaker and Robinson, The Calculus of Observations, pp.79–81.]]

13

Amer. Math. Monthly, 59(1952) 640.

4508. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn, New York

Find a polynomial F (x) of lowest degree such that F (x)+ω s is divisible by (xω s ) r for

, p 1, where ω is a primitive p th root of unity and r is a given positive

integer. (This generalizes a problem in Goursat-Hedrick, A Course in Mathematical Analysis, v.1, p.32.)

Amer. Math. Monthly, 61(1954) 127–128.

Solution by Chih-Yi Wang, University of Minnesota. Since F (x) is divisible by (x p 1) r1 , and the binomials x ω s are relatively prime to one another, it is evident that the degree of the polynomial F (x) cannot be lower than p(r 1) + 1. Let

s = 0, 1, 2,

F (x) = a(x p 1) r1

where a (

x we get

= 0) is some constant which has to be determined. By integrating from 0 to

F (x) F (0) = a x (t p 1) r1 dt

0

But F (ω s ) + ω s = 0 for s =

, p 1, so that

ω s F (0)

=

=

=

ω s a(t p 1) r1 dt

0

ω s a

r1

k=0

(1) k r 1

k

ω s a 1 (t p 1) r1 dt

0

p[(r 1) k] + 1

1

s = 0, 1,

, p 1.

These p equations are satisﬁed if and only if

F (0) = 0,

a = 1 1 (t p 1) r1 dt

0

Hence the required polynomial is

F(x) = x (t p 1) r1 dt 1 (t p 1) r1 dt

0

0

[[Also solved by X, Y, M. S. Klamkin, Z, and the Proposer — who was Murray Klamkin!!]]

14

Amer. Math. Monthly, 59(1952) 643 Polynomials with Positive Coeﬃcients

4411 [1951, 343]. Proposed by R. M. Cohn, Rutgers University

If a polynomial equation f (x) = 0, with integral coeﬃcients has no positive roots, there exists a polynomial g(x) with integral coeﬃcients such that all coeﬃcients of f (x) · g(x) are positive.

Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn. It will suﬃce to prove

the

the coeﬃcients of q(x) · p(x) will be positive if

(a, b > o, a 2 < 4b). Let p(x) = (1 + x) k . Then all

theorem for q(x) = x 2 ax + b,

k

r

a

r 1 + b

k

r 2 > 0

k

(1)

for r = 1, 2,

f (x) can be factored into linear factors like x + c, c 0, and quadratic factors like q (x). We may then take g (x) to be (1 + x) K where K is the sum of the k s determined as above for the individual quadratic factors of f (x). Since the coeﬃcients of f (x) are integers, the coeﬃcients of f (x) · g(x) will be positive integers.

Also solved by [5 others and] the Proposer

Editorial Note. The existence of suitable k may be seen as follows. (1) reduces to

, k + 1. This is always possible for k suﬃciently large.

(k r + 2)(k r + 1) ar(k r + 2) + br(r 1) >

0

which is true if

2k > (2 + a)r 3 + 1 + (2a + 4b)r (4b a 2 )r 2

(2)

and the radical is real; if the radical is imaginary (1) is true for all k. Evidently the right member of (2) has a maximum value and we need only choose k greater than this maximum.

[L. J. ]Paige and George ]Piranian refer to a proof by E. Meissner (Math. Annalen, v.70(1911) p.223) and to the following generalization by D. R. Curtiss (Math. Annalen, v.73(1913) p.424): If f (x) is any polynomial with all its coeﬃcients real, there exists polynomials f 1 (x) such that when the product f 2 (x) = f 1 (x) · f (x) is arranged according to ascending or descending powers of x, the number of variations of sign presented by its coeﬃcients is exactly equal to the number of positive roots of f (x). See also P´olya and Szeg¨o, Aufgaben und Lehrsatze, v.II, problem 190, section 5.

15

Amer. Math. Monthly, 59(1952) 648–649. A Diophantine Equation

4448 [1951, 343]. Proposed by Jekuthiel Ginsburg, Yeshiva College, New York City

Solve in positive integers

z 4 = ax 2 + by 2 a + b

where a and b are given integers.

I. Solution by M. S. Klamkin, Polytechnic Institute of Brooklyn, New York. The given equation will be satisﬁed if

an(z 2 + x) = m(y z 2 )

m(z 2 x) = bn(y + z 2 )

m and n being arbitrary integers. Therefore

x :

y

: z 2 = |m 2 2bmn abn 2 | : |m 2 + 2amn abn 2 | : (m 2 + abn 2 )

is a solution provided the constant of proportionality, k, is so chosen that k(m 2 + abn 2 ) is a perfect square.

Other solutions may be obtained by solving z 2 = m 2 +abn 2 . See L. E. Dickson, History of the Theory of Numbers, v.2, p.425. One form of the solution is

m : n : z = |p 2 abq 2 | : 2pq

16

:

(p 2 + abq 2 )

Amer. Math. Monthly, 59(1952) 702.

4514. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn

ψ(t) = constant and ψ(t) = |t| are solutions of the integral equation

1

2ψ(t) =

1

ψ(2tx) dx

as is easily veriﬁed. Are there any other solutions?

Amer. Math. Monthly, 61(1954) 203.

Solution by J. E. Wilkins, Jr., Nuclear Development Associates, Inc., White Plains, N.Y. There are others. To ﬁnd additional solutions, substitute |t| a for ψ(t). This function will satisfy the integral equation if and only if 2 a = a +1. This transcendental equation has exactly two real roots, namely 0 and 1, and has inﬁnitely many complex roots

α n ± n (log 2) 1

such that

α n = 1 + β n (log 2) 1 cot β n

2β n (log 2) 1 exp(β n cot β n ) = sin β n

2nπ < β n < (4n + 1)π/2

(n = 1, 2,

Also solved by [7 others and] the Proposer.

Editorial Note. As shown also by the other solvers, there exist no real solutions of the integral equation, under the assumption that ψ(x) is of class C 1 on [0,1], other than linear combinations of the solutions cited by the Proposer.

.). For example, β 1 = 7.454087, α 1 = 3.545368 ± 10.75397i.

17

Amer. Math. Monthly, 60(1953) 40.

 E 1049. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn If a uniform thin rod of length L is perpendicular to and touching the earth’s surface

at one end, ﬁnd the distance between the centre of gravity and the centre of mass of the rod.

Centre of Gravity of a Vertical Rod

Solution by M. Morduchow, Polytechnic Institute of Brooklyn

Let x be distance measured along the rod from the earth’s surface. Also, let R be the radius and M the mass of the earth, while ρ is the mass per unit length of the rod. Then, by Newton’s inverse-square law, the total force (directed towrds the earth’s centre) acting on the rod will be

F = L GM ρ(R + x) 2 dx = GMm/R(R + L)

0

where G is the gravitational constant, and m = ρL is the mass of the rod. If the centre of gravity is at x = x g , then by deﬁnition we require that F = GMm/(R + x g ) 2 . Therefore (R + x g ) 2 = R(R + L), whence

x g = R(R + L) R

Since the centre of mass is at x = x m = L/2, the centre of gravity will be below the centre of mass, abd the distance between the two centres will be

x m x g = L/2 R[(1 + L/R) 1/2 1]

If L/R 1, then expansion by the binomial theorem to second powers of L/R yields

the approximate result

x m x g (1/8)(L/R)L.

Also solved by [13 others and] the Proposer.

All of these solutions were not the same. [Julian ]Braun, [A. R. ]Hyde, [L. V. ]Mead, [J. V. ]Whittaker and the proposer took the distance x g to be

x g =

0

0

x(R + x) 2 dx

L

L (R + x) 2 dx

= (R/L)(R + L) ln(1 + L/R) R.

[Azriel ]Rosenfeld took the centre of gravity of the rod as that point for which the

weight of the portion of the rod above the point is equal to the weight of the portion

of the rod below the point. He found

x g = 2RL/(4R + L).

18

All other solutions werelike Murduchow’s. Here, for a rod a mile long, the distance between the centres is about 2 inches.

[H. W. ]Smith called attention to Kellogg, Foundations of Potential Theory, p.4.

Amer. Math. Monthly, 60(1953) 186–187.

[[There’s a Classroom Note, D. E. Whitford and M. S. Klamkin, On an elementary derivation of Cramer’s rule.]]

Amer. Math. Monthly, 60(1953) 188.

E 1057. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn

Find the sum of the ﬁrst n terms of the series

sec θ + (sec θ sec 2θ)/2 + (sec θ sec 2θ sec 4θ)/4 + · · · .

Amer. Math. Monthly, 60(1953) 628.

Solution by J. R. Hatcher, Fisk University. Using the identities sec α = 2 sin α/ sin 2α and csc α = cot α/2 cot α, we conclude that the sum S n (θ) of the ﬁrst n terms is

 S n (θ) = 2 sin θ(csc 2θ + csc 4θ + · · · csc 2 n θ) = s sin θ(cot θ − cot 2 n θ) = [2 sin(2 n − 1)θ]/[sin 2 n θ].

[F. ]Underwood pointed out that the problem is essentially Ex.10, p.125 of Plane

Trigonometry, Part II, by S. L. Loney (1908).

19

Amer. Math. Monthly, 60(1953) 423.

4546. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn, New York

Evaluate

I =

0

sin mx sin nx sin m+1 x sin n + 12x x 2 sin 2 x

2

2

2

2

dx

where m and n are integers and m n.

Amer. Math. Monthly, 61(1954) 649.

Solution by J. V. Whittaker, University of California, Los Angeles. This integral is merely

0

1

x

2

m

n

r=1

s=1

sin rx sin sx dx

Integrating by partsand applying the sum and diﬀerence formulas, we obtain a known form:

0

sin rx sin sx

x

2

dx

=

=

0

πs/2

r cos rx sin sx + s sin rx cos sx

x

dx

(r s)

Summing over r and s, we ﬁnd the value of I to be (π/12)n(n + 1)(3m n + 1).

Also solved by [6 others and] the Proposer.

20

Amer. Math. Monthly, 60(1953) 632.

4561. Proposed by M. S. Klamkin, Polytechnic Institute of Brooklyn, New York

Prove

S 2,p +

r

n=1

n 2 n + p

p

1

= S 2,r +

p

n=1

n 2 n + r

r

1

where S 2,p = n=1 p 1/n 2 .

Amer. Math. Monthly, 62(1955) 49.

Solution by Leonard Carlitz, Duke University. Let p be an arbitary, ﬁxed integer. For r = 1, the proposed relation reduces to

S 2,p +

which is evidently true since

p

n=1

1

n 2

p

n=1

1

n 2 (n + 1) =

1

p + 1 = 1 +

p

n=1

1

n 2 (n + 1)

p

n=1

1

n(n + 1) =

p

n n + 1 = 1

1

1

1

p + 1

Assuming now that the stated result holds for r 1, we have

S 2,r +

=

=

=

p

n=1

n 2 n + r

r

1

S 2,r1

p

n=1

n 2 n + r 1 r 1

1

1

r 2

p

n=1

(